2007
DOI: 10.1038/sj.onc.1210616
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuins: critical regulators at the crossroads between cancer and aging

Abstract: Sirtuins (SIRTs 1À7), or class III histone deacetylases (HDACs), are protein deacetylases/ADP ribosyltransferases that target a wide range of cellular proteins in the nucleus, cytoplasm, and mitochondria for post-translational modification by acetylation (SIRT1, -2, -3 and -5) or ADP ribosylation (SIRT4 and -6). The orthologs of sirtuins in lower organisms play a critical role in regulating lifespan. As cancer is a disease of aging, we discuss the growing implications of the sirtuins in protecting against canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
466
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 540 publications
(475 citation statements)
references
References 149 publications
(239 reference statements)
4
466
0
5
Order By: Relevance
“…There is also a therapeutic interest in the sirtuins as they have been linked to the correlation between caloric restriction and life span extension in model organisms such as yeast, worms, flies, fish and rodents; in mammals, sirtuin activity has been linked to counteracting age-associated diseases such as type II diabetes, obesity and neurodegenerative disorders (Wood et al, 2004a, b;Kobayashi et al, 2005;Parker et al, 2005;Anekonda and Reddy, 2006;Baur et al, 2006). The association of sirtuins with aging and diseases is discussed in greater detail in this issue of Oncogene (Saunders and Verdin, 2007). Interestingly, several HDACs have been shown to target non-histone proteins for deacetylation as well.…”
Section: Overview Of Hdacsmentioning
confidence: 99%
“…There is also a therapeutic interest in the sirtuins as they have been linked to the correlation between caloric restriction and life span extension in model organisms such as yeast, worms, flies, fish and rodents; in mammals, sirtuin activity has been linked to counteracting age-associated diseases such as type II diabetes, obesity and neurodegenerative disorders (Wood et al, 2004a, b;Kobayashi et al, 2005;Parker et al, 2005;Anekonda and Reddy, 2006;Baur et al, 2006). The association of sirtuins with aging and diseases is discussed in greater detail in this issue of Oncogene (Saunders and Verdin, 2007). Interestingly, several HDACs have been shown to target non-histone proteins for deacetylation as well.…”
Section: Overview Of Hdacsmentioning
confidence: 99%
“…Sirtuins are a family of protein deacetylases and adenosine diphosphate (ADP)-ribosyltransferases whose functions require NAD þ (Saunders and Verdin, 2007). Among them, SIRT1 has the highest homology to yeast Sir2 (silent information regulator 2) that extends lifespan under calorie restriction (Lin et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…the role of sIrt1 in cell survival is achieved by deacetylation of key cell cycle molecules and apoptosis regulatory proteins, including Foxo family proteins (3), Ku70 (4), NF-κB (5), and p53 (6,7). Up-regulation of sIrt1 induces deacetylated inactivation of p53, which allows proliferation of cells in the presence of damaged DNA such that mutations accumulate, including those in p53 itself, leading to disruption of the cell cycle control and promotion of tumor progression (6)(7)(8)(9)(10)(11). recent studies have demonstrated overexpression of sIrt1 in cancer tissue, compared with normal tissue, suggesting that sIrt1 may act as a tumor promoter (9,(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%